85.5k views
4 votes
HELP!!!!!!!a system of equation is shown below 6x - 2y equals 3 . and 5x + 3y equals 4. would you solve by substitution or elimination? and why

User Fgrehm
by
5.4k points

2 Answers

6 votes

Answer:

elimination because if you multiply the first equation by 3 and the second by 2 you can eliminate your y's


User Koders
by
5.8k points
6 votes

Answer:

see below

Explanation:

6x-2y =3

5x+3y =4

I would use elimination

To solve for one variable in either equation, you would end up with fractions, and fractions are hard to work with.

Take the firs equation. to solve for y

6x -2y =3

-2y = -6x+3

y = -6x/-2 +3/-2

The last term is a fraction and then we substitute it into the other equation.


With elimination

Multiply the first equation by 3 and the second equation by 2

18x -6y =9

10x+6y = 8

------------------------

28x = 17

We do not deal with fraction until we solve

User Artik
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.